Experimental study of the interlaminar fracture of composite materials in mode III by MSCB test. (1st February 2020) - Tawk, I.; Rishmany, J.; Saba, J.; Navarro, P.; Ferrero, J.-F.
Abstract: This paper focuses on the study of interlaminar fracture of composite materials in mode III using the Modified Split Cantilever Beam (MSCB) test. MSCB test is applied to investigate the dependency of the mode III energy release rate on geometric parameters (specimen width, and thickness), initial crack length, loading condition and crack front material layup. A non perforated release film is introduced to create delamination at the mid-plane of the tested specimens. Three sets of samples (a total of 56 samples) are fabricated and tested from Unidirectional Glass fibers. The length of the specimens is 154 mm. The first set of tests is conducted for three different widths (35 mm, 20 mm, 12 mm) to select the most appropriate width that leads to a crack initiation prior to specimen failure. The remaining sets of tests are conducted with different loading conditions, different thickness, different initial crack length, and different lay up orientations at the crack front (0/0, +45/−45, 0/45, and 0/90). Results show that both width selection and load configuration are of extreme importance for the success of the test. The energy release rate (GIIIc ) increases with increasing thickness and width. The stacking orientation at the crack front shows minor influence on GIIIc .